To analyze the arithmetic sequence given by the formula \( a_n = 6 + (n - 1) \cdot 8 \), we can first rewrite it in a more standard form:
\[ a_n = 6 + 8(n - 1) \] \[ a_n = 6 + 8n - 8 \] \[ a_n = 8n - 2 \]
This shows that the arithmetic sequence can be expressed in the form of a linear function where it has the structure \( y = mx + b \) with \( m = 8 \) and \( b = -2 \).
Now, looking at the provided options:
- \( y = 2x - 8 \)
- \( y = 6x + 8 \)
- \( y = 8x + 6 \)
- \( y = 8x - 2 \)
The correct choice that matches the structure of the arithmetic sequence \( a_n = 8n - 2 \) is:
\( y = 8x - 2 \)
So, the answer is \( y = 8x - 2 \).